1994
DOI: 10.1002/1520-6777(1994)13:3<219::aid-nau1930130303>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pressure changes in the lower urinary tract during coughing with special reference to the demands on the pressure recording equipment

Abstract: The exact demands on urodynamic equipment for measurement of coughs and cough associated pressure changes in the lower urinary tract have been analyzed from high‐speed pressure recordings using a double microtip transducer and a storage oscilloscope. The equipment was tested in vitro by the step‐test method. The natural frequency response was 175.6 Hz and the rise‐time 2.5 ms, resulting in accurate measurements of frequencies up to about 60 Hz which is way above the clinically measured frequencies. Four men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Kim et al conducted a frequency assessment of select urodynamic signals, and concluded that CLPP and VLPP tests occur with frequency contributions as high as 14 and 7 Hz, respectively. The clinical urodynamic signals collected from the literature for our study show the relevant time to peak pressure as approximately 0.2–0.25 sec (or 4–5 Hz) for CLPPs and 1–2 sec (or 0.5–1 Hz) for VLPPs . This is consistent with the suggestion by Hogan et al that valsalva be defined as lasting more than 2 sec.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Kim et al conducted a frequency assessment of select urodynamic signals, and concluded that CLPP and VLPP tests occur with frequency contributions as high as 14 and 7 Hz, respectively. The clinical urodynamic signals collected from the literature for our study show the relevant time to peak pressure as approximately 0.2–0.25 sec (or 4–5 Hz) for CLPPs and 1–2 sec (or 0.5–1 Hz) for VLPPs . This is consistent with the suggestion by Hogan et al that valsalva be defined as lasting more than 2 sec.…”
Section: Discussionsupporting
confidence: 91%
“…The CLPP signals obtained from literature have time to peak pressure 0.2–0.25 sec, while the VLPP signals have time to peak pressure 1–2 sec . Thus, VLPPs are in the range of slowly changing signals in which ACCs measured peak pressures similar to those measured simultaneously by WFCs.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Cough tests are generally considered to generate the fastest changing (i.e., highest frequency) intravesical pressure signal in UDS testing. Therefore, Thind et al assessed the frequency spectrum of cough tests in six healthy volunteers: four men and two women . They found that 99% of the power of the bladder pressure signal in a cough occurs at frequencies of 9 Hz or less.…”
Section: Methodsmentioning
confidence: 99%